Hubungan Matan dan Syarah Ta’līm Al-Muta’allim Ṭarīq Al-Ta’allum dengan Daulah ‘Aliyyah Utsmaniyyah serta Implikasinya dalam Pendidikan Islam di Nusantara - Tatang Hidayat; Syahidin Syahidin; Arif Noor Dhaiman (Islam Transformatif : Journal of Islamic Studies, 2020)
The purpose of this study was to analyze the relationship of matan and syarah Ta'līm al-Muta'allim Ṭarīq al-Ta'allum with Daulah 'Aliyyah Uthmaniyyah and its implications in Islamic education in the Archipelago.  Islamic education is fixed in terms of teaching materials and learning methods, because it is part of sharia law that relies on evidence, while uslub (technique) and its facilities are constantly evolving. From this point of view, the analysis of the Book of Ta'līm al-Muta'allim Tarīq al-Ta'allum and  its implications in Islamic education in the Archipelago can be reviewed. This research uses qualitative approaches and descriptive methods. Based on the results of the research, the book ta'lîm al-Muta'allim Tarīq al-Ta'allum and its syarah reached the Archipelago through the relationship of Mecca as part of the Territory (governorate level/ Province) of Daulah 'Aliyyah Ottoman who was the Caliphate of the Muslims at that time with the Jawi Scholars who studied there. The Book of Ta'lîm al-Muta'allim Ṭarīq al-Ta'allum and its syarah are clearly seen in the Salafiyyah (Traditional) Pesantren Curriculum especially in Java Island. It can be determined that the "spirit" of the boarding school is the concept of Islamic Education described in the book of Ta’lîm al-Muta’allim Ṭarīq al-Ta'allum and its syarah, especially related to the adab to science and teachers.  Tujuan penelitian ini untuk menganalisis hubungan matan dan syarah Ta'līm al-Muta'allim Tarīq al-Ta'allum dengan Daulah ‘Aliyyah Utsmaniyyah serta implikasinya dalam pendidikan Islam di Nusantara. Pendidikan Islam bersifat tetap dari aspek materi ajar dan metode belajarnya, karena bagian dari hukum syariah yang bersandar pada dalil, sedangkan uslub (teknik) dan sarananya senantiasa berkembang. Dari sudut pandang inilah, analisis kitab Ta’lîm al-Muta’allim Tharîq at-Ta’allum dan implikasinya dalam pendidikan Islam di Nusantara dapat ditinjau. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Berdasarkan hasil penelitian, kitab Ta’lîm al-Muta’allim Tarīq al-Ta'allum dan syarah-nya sampai ke Nusantara melalui hubungan Mekkah sebagai bagian Wilayah (setingkat Kegubernuran/Provinsi) dari Daulah 'Aliyyah Utsmaniyyah yang merupakan Kekhalifahan-nya kaum Muslimin saat itu dengan para Ulama Jawi yang belajar di sana. Kitab Ta’lîm al-Muta’allim Tarīq al-Ta'allum dan syarah-nya jelas terlihat dalam Kurikulum Pesantren Salafiyyah (Tradisional) terutama di Pulau Jawa. Dapat ditetapkan bahwa "ruh" dari pondok pesantren adalah konsep Pendidikan Islam yang dijelaskan dalam kitab Ta’lîm al-Muta’allim Tarīq al-Ta'allum dan syarahnya, terutama terkait adab terhadap ilmu dan guru.